Relationship between neck circumference, insulin resistance and arterial stiffness in overweight and obese subjects. (September 2017) - Fantin, Francesco; Comellato, Gabriele; Rossi, Andrea P; Grison, Elisa; Zoico, Elena; Mazzali, Gloria; Zamboni, Mauro
Background: Only a few studies have investigated the relationship between neck circumference and cardiometabolic risk. The aim of this study was to assess the relationships between neck circumference, waist circumference, metabolic variables and arterial stiffness in a group of overweight and obese subjects evaluating a possible independent role of neck circumference in determining arterial stiffness. Methods and results: We studied 95 subjects (53 women) with an age range of 20–77 years and body mass index range from 25.69 to 47.04 kg/m 2 . In each subject we evaluated body mass index, waist, hip and neck circumference, systolic and diastolic blood pressure, insulin, fasting glucose, cholesterol, low-density lipoprotein and high-density lipoprotein cholesterol and triglycerides. Arterial stiffness was assessed by carotid-femoral pulse wave velocity (PWVcf) and carotid-radial pulse wave velocity (PWVcr). Both PWVcf and PWVcr were higher in subjects with high values of neck circumference compared with subjects with normal values of neck circumference. Subjects with high values of neck circumference and abdominal obesity presented higher values of mean arterial pressure, PWVcr and homeostasis model assessment (HOMA) index and lower values of high-density lipoprotein than subjects with only abdominal obesity. Two models of stepwise multiple regression were performed in order to evaluate the combined effect of independent variables on arterial stiffness. In the first model PWVcf was considered a dependent variable, and age, gender, systolic blood pressure, triglycerides, high-density lipoprotein cholesterol, waist circumference, neck circumference, HOMA index and the use of anti-hypertensive medications were considered independent variables. Age, systolic blood pressure, triglycerides and waist circumference were significant predictors of PWVcf, explaining 65% of its variance. In the second model, in which PWVcr was considered a dependent variable, neck circumference and gender were significant predictors of PWVcr, explaining 24% of its variance. Conclusions: These findings emphasise the need to measure not only waist but even neck circumference to better stratify and identify individuals at increased cardiometabolic risk, as upper-body subcutaneous fat is a novel, easily measured fat depot.